Asymptotic Equivalence of Probabilistic Serial and Random Priority Mechanisms. - Che, Yeon-Koo; Kojima, Fuhito (Econometrica, 2010)
The writers explored random priority—random serial dictatorship—mechanism as a common method for assigning objects. The mechanism was strategy-proof and easy to apply. However, this mechanism was inefficient, because all agents might be made better off by another mechanism that improves their chances of acquiring more preferred objects. This form of inefficiency was eliminated by a method called probabilistic serial, but this method was not strategy-proof. The writers showed that these mechanisms become equivalent when the market becomes large. Given a set of object types, the random assignments in these mechanisms converge to each other as the number of copies of each object type approaches infinity. The inefficiency of the random priority mechanism became small in large markets.